Ethyl 4-(2-hydroxyethylamino)-3-nitrobenzoate - Abdul Rahim, Aisyah Saad; Abd Hamid, Shafida; Narendra Babu, Shivanagere Nagojappa; Loh, Wan-Sin; Fun, Hoong-Kun (International Union of Crystallography, 2010)
In the title compound, C11H14N2O5, the molecular structure is stabilized by an intramolecular N—H O hydrogen bond, which generates an S(6) ring motif. The nitro group is twisted slightly from the attached benzene ring, forming a dihedral angle of 5.2 (2). In the crystal packing, intermolecular O—H O and C—H O hydrogen bonds link the molecules into a three-dimensional network. The crystal studied was a nonmerohedral twin, the refined ratio of the twin components being 0.264 (2):0.736 (2).